Adopting the Healthcare Failure Mode and Effect Analysis to Improve the Blood Transfusion Processes - Su, Chao-Ton; Chou, Chia-Jen; Hung, Sheng-Hui; Wang, Pa-Chun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
The aim of this study is to conduct the healthcare failure mode and effects analysis (HFMEA) to evaluate the risky and vulnerable blood transfusion process. By implementing HFMEA, the research hospital plans to develop a safer blood transfusion system that is capable of detecting potentially hazardous events in advance. In this case, eight possible failure modes were identified in total. Regarding the severity and frequency, seven failure modes were identified to have hazard scores higher which are than 8. Five actions were undertaken to eliminate the potential risk processes. After the completion of HFMEA improvement, from the end of July, 2008 to December 2009, two adverse events occurred during the blood transfusion processes and the error rate is 0.012%. The HFMEA proves to be feasible and effective to predict and prevent potentially risky transfusion processes. We have successfully introduced information technology to improve the whole blood transfusion process.